Transform Active cities facing the ecological transition: Cha(lle)nges, strategies and practices in the EU panorama - Pultrone, Gabriella (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Climate change is the latest a threat multiplier, since it worsens most of humanity’s most pressing environmental, societal and economic challenges. Anyway, growing urbanisation brings both opportunities and challenges related to the ongoing transition process, since cities are at the forefront of changes and challenges. Regeneration of urban areas is a significant priority, which needs to take into account environmental quality, social justice and sustainable development. Transforming cities and regions into vibrant, sustainable, and resilient living places has become a key global priority. In the light of the above, the article – in the context of ongoing research activities – focuses on the ecological transition in the EU panorama, highlighting the active and decisive role of cities, with reference to some significant case studies in the implementation of Green and Nature-based Solutions (NBS) through an integrated, forward-looking, and broad-based planning approach. It is structured in three main parts. The first part places the theme in the international scientific context. The second, with reference to the EU panorama, highlights the fundamental role of NBS with reference to the methodological approach, and latest and most innovative ongoing policies, strategies and practices. The third part consists of the discussion and the consequent concluding remarks.